2017
DOI: 10.1136/injuryprev-2017-042499
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of neighbourhood slow zones in New York City

Abstract: While additional causal models are needed, NSZs appeared to be an effective and cost-effective means of reducing road casualties. Our models also suggest that NSZs may save more money than they cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Several studies have specifically focused on the safety impacts of traffic-calming neighbourhoods at 30 km/h (Bunn et al, , 2009Elvik, 2001;Ewing & Edwards, 2009;Hass-Klau, 2015;Inada, Tomio, Nakahara, & Ichakawa, 2020;Jiao, Kim, Hagen, & Muennig, 2019;Li & Graham, 2016;NCCHPP, 2011;Tefft, 2013). The overwhelming consensus of these studies is that traffic-calming reduces speeds and volumes of motorised traffic, discourages through traffic, reduces pedestrian and cyclist injuries, and reduces air pollution and noise.…”
Section: Speed Limits Traffic Calming Home Zones Shared Streets Cmentioning
confidence: 99%
“…Several studies have specifically focused on the safety impacts of traffic-calming neighbourhoods at 30 km/h (Bunn et al, , 2009Elvik, 2001;Ewing & Edwards, 2009;Hass-Klau, 2015;Inada, Tomio, Nakahara, & Ichakawa, 2020;Jiao, Kim, Hagen, & Muennig, 2019;Li & Graham, 2016;NCCHPP, 2011;Tefft, 2013). The overwhelming consensus of these studies is that traffic-calming reduces speeds and volumes of motorised traffic, discourages through traffic, reduces pedestrian and cyclist injuries, and reduces air pollution and noise.…”
Section: Speed Limits Traffic Calming Home Zones Shared Streets Cmentioning
confidence: 99%
“…In addition, injuries to vulnerable road users (pedestrians and cyclists) were reduced by over half (55%) [27]. Another study from New York City reported that road casualties dropped by 8.74% after implementation of neighborhood slow zones (20 mph speed limit areas) in 2011 [9]. This study also found a cost-savings of $15 USD per resident to the healthcare system when slow zones were in place.…”
Section: Crash Risk Reduction and Injury Severitymentioning
confidence: 67%
“…A meta-analysis of impact speed and pedestrian fatality risk supports setting speed limits of 30-40 km/h for high pedestrian activity areas as the risk of a fatality reaches 5% at an estimated impact speed of 30 km/h [8]. Although many studies report a reduction in severe PMVC injuries and crash risk after lowering speed limits, speed limit reductions have not been well studied using controlled quasi experimental designs [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Their study used pre-post data and compared the costs of the program with the effect in terms of bicycle-related head injury and deaths. Other studies, such as Peters and Anderson (2012) , Wijnen et al (2013) and Jiao et al (2019) , applied CEA to measure the efficacy of traffic calming aiming at reducing accidents costs. Others such as Gunn et al (2014) have focused on the effects of sidewalks to increase levels of transport walking and related health effects, while Gu et al (2016) analyzed the cost-effectiveness of bicycle lanes as means to both improve health of the general population and reduce crashes.…”
Section: Applicationsmentioning
confidence: 99%